PENGARUH INFRASTRUKTUR PEMBANGUNAN TERHADAP PERTUMBUHAN EKONOMI JAWA TIMUR - Herlina Panama; Idah Zuhroh; Ida Nuraini (Program Studi Ekonomi Pembangunan, 2019)
This study aims to determine the effect of Infrastructure for Road, Electricity, Water, Education, and Health Development on the economic growth of the study of the North-South Corridor of East Java Province in 2010-2017. The data used in this study is to use secondary data taken from 2010-2017. This study uses a multiple linear regression tool using panel data method by testing hypotheses such as F test, t test, and Determination Coefficient R2. Based on the results of the study, it shows that Water, Electricity and Education Development Infrastructure has an effect on economic growth in the North-South Corridor Area of East Java while Road and Health Infrastructure does not affect Economic Growth in the North Corridor- South East Java Province. Water infrastructure has a positive and significant effect on economic growth. Electricity infrastructure has a positive and significant effect on economic growth. Educational infrastructure has a positive and significant effect on economic growth. Health Infrastructure has a negative and significant effect on economic growth. Based on the results of this study, it is necessary to have policies that can encourage infrastructure to help increase economic growth.